PENERAPAN TARIAN TEA EKU MELALUI PROBLEM BASED LEARNING UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR SISWA - Sofia Sa'o; Finsensius Yesekiel Naja; Maria Fatima Mei (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Mathematics learning in schools has not been linked to cultural concepts. Tea-eku dance is a cultural dance that contains a mathematical concept, the movement of the tea-eku dance contains a geometric concept. The purpose of this study is to apply tea-eku exercises through problem-based learning in increasing student interest and learning outcomes. The population in this study were all class VII students of SMP Adyaksa Ende for the 2022-2023 academic year. The sample in this study was class VII A as the experimental class and class VII B as the control class, each consisting of 13 students. The results of this study indicated that the learning interest of the control class students ranged from 55-78, while the experimental class with tea-eku dance media had scores ranging from 68 to 144 with an average score of 132.05 and a standard deviation. of 41,744. While student learning outcomes based on the results of the normality test using the Kolmogorov-Smirnov formula obtained normally distributed data (P = 0.000 <0.05). It can be interpreted that the application of tea-eku dance through problem-based learning can increase student interest and learning outcomes, seen from the statistical results F = 14.29 and F table = 4.28 with dk quantifier = 1 and dk denominator = 23, giving a value that significant.